Broadly protective Bovine Parainfluenza-3 virus and Bovine Viral Diarrhea virus vaccine - Sang, Huldah (My University, 2025)
Bovine Parainfluenza-3 virus (BPI3V) and Bovine Viral Diarrhea Virus (BVDV) are major respiratory pathogens contributing to Bovine Respiratory Disease Complex, leading to significant economic losses. While good management practices and biosecurity measures are important, vaccination remains the most effective control strategy. However, existing commercial BPI3V vaccines, based on genotype A strains, confer protection against some, but not all, genotype A strains and elicit low neutralizing titers against genotypes B and C. Similarly, current commercial BVDV vaccines, formulated using BVDV-1a and BVDV-2a strains, confer partial protection against strains from homologous genotypes and low neutralization titers against heterologous and emergent genotypes. This Thesis presents studies aimed at developing a live vaccine capable of inducing broad protection against BPI3V and BVDV strains. In the first study, a BPI3V vaccine vector based on a genotype C strain was developed and validated for in vitro attenuation, transgene expression, and genetic stability. Novel mosaic BPI3V Fusion (F2) and Hemagglutinin-Neuraminidase (HN2) antigens, derived from consensus protein sequences of BPI3V genotypes A, B, and C, were used to develop a recombinant prototype vaccine, designated rBPI3Vc[subscript mut]F2HN2. Calves vaccinated intranasally with the rBPI3Vc[subscript mut]F2HN2 vaccine exhibited robust systemic and mucosal IgG responses against all the three BPI3V genotypes, which were significantly amplified after boosting. Notably, the prototype vaccine induced significantly higher (p<0.0001) neutralizing antibodies against BPI3V genotypes A-C compared to a commercial vaccine, and the robust IgG responses were primarily primed and expanded by the mosaic F2HN2 antigens. Following challenge with wild-type BPI3V genotype C virus, the rBPI3Vc[subscript mut]F2HN2-vaccinated calves shed the least amount of virus in nasal fluids, had lower viral loads in their blood, and exhibited minimal pulmonary lesions. These findings demonstrate that the live rBPI3Vc[subscript mut]F2HN2 prototype vaccine is a promising candidate for inducing broad BPI3V protection compared to the current commercial vaccine. In the second study, a BPI3Vc-vectored BVDV prototype vaccine was developed using novel mosaic BVDV E2-NS2-5¹⁻² antigens. These antigens, designed from the consensus of all BVDV-1a, -1b, -2a, -2b, and -2c protein sequences, were used to generate recombinant BPI3Vc[subscript mut]E2-NS2-5¹⁻² viruses, collectively designated as rBPI3Vc[subscript mut]BVDV. Intranasal immunization of calves with the rBPI3Vc[subscript mut]BVDV prototype vaccine elicited higher IgG responses against BVDV-1b California and TGAC, with significantly higher viral neutralizing titers (California: p=0.0031, TGAC: p=0.0002) compared to a commercial vaccine. Immunized calves also elicited significantly higher VN titers against BVDV-2a strains 296NC (p=0.0006, 890 (p=0.0020), 296C (p=0.0464), A125 (p=0.0018), and 1373 (p=0.0025). Following challenge with BVDV-1b California, the rBPI3Vc[subscript mut]BVDV vaccinees exhibited a steady weight gain, lower lymphopenia, lower blood viral load, and fewer gross lesions. Overall, data generated from this thesis support using the live-attenuated BPI3Vc-vector for development of contemporary broadly protective BPI3V and BVDV vaccines that can easily be upgraded for improved disease management and cattle productivity.
Keywords: Bovine Parainfluenza-3 virus; Vector; Bovine Viral Diarrhea virus; Surface display; Broadly neutralizing antibody; Cross-protection